Lesion Genotype Modifies High-Fat Diet Effects on Endometriosis Development in Mice - Heard-Lipsmeyer, Melissa E.; Alhallak, Iad; Simmen, Frank A.; Melnyk, Stepan B.; Simmen, Rosalia C. M. (Frontiers in Physiology, 2021)
Endometriosis is a chronic, estrogen-dependent gynecologic disorder that affects reproductive-age women and to a lesser extent, post-menopausal women on hormone therapy. The condition is associated with systemic and local immune dysfunctions. While its underlying mechanisms remain poorly understood, endometriosis has a genetic component and propensity for the disease is subject to environmental, nutritional and lifestyle influences. Previously, we showed that high-fat diet (HFD) increased ectopic lesion numbers, concurrent with systemic and peritoneal changes in inflammatory and oxidative stress status, in immunocompetent recipient mice ip administered with endometrial fragments null for Krüppel-like factor 9 (KLF9) gene. Herein, we determined whether HFD modifies lesion parameters, when recipient peritoneal environment is challenged with ectopic wildtype (WT) endometrial fragments, the latter simulating retrograde menstruation common in women during the menstrual period. WT endometrium-recipient mice fed HFD (45% kcal from fat) showed reduced lesion incidence, numbers and volumes, in the absence of changes in systemic ovarian steroid hormone and insulin levels, relative to those fed the control diet (CD, 17% kcal from fat). Lesions from HFD- and CD-fed recipients demonstrated comparable gene expression for steroid hormone receptors (Esr, Pgr) and cytokines (Il-6, Il-8, CxCL4) and similar levels of DNA oxidative biomarkers. HFD moderately altered serum (3-nitrotyrosine, Met/Hcy) and peritoneal (GSH/GSSG) pro-oxidative status but had no effect on peritoneal inflammatory (TNFα, sTNFR1) mediators. Results indicate that lesion genotype modifies dietary effects on disease establishment and/or progression and if translated, could be important for provision of nutritional guidelines to women with predisposition to or affected by endometriosis.